Tree‐ring‐based precipitation reconstruction in southern Kazakhstan, reveals drought variability since A.D. 1770. (28th April 2016) - Zhang, Ruibo; Shang, Huaming; Yu, Shulong; He, Qing; Yuan, Yujiang; Bolatov, Kainar; Mambetov, Bulkajyr T.
ABSTRACT: In this article, we developed a tree‐ring‐width chronology of Schrenk spruce ( Picea schrenkiana Fisch. et Mey) in southern Kazakhstan. Climate‐growth response result showed that the precipitation from the previous June to current May was the principal limited factor of radial growth. We also obtained a 246‐year reconstruction of June–May precipitation in southern Kazakhstan. The reconstruction explains 39.7% of the variance in precipitation records during the 1902–2013 calibration periods. In addition, the precipitation over the past 246 years in southern Kazakhstan has experienced six wetter periods and seven drier ones, and the extreme drought years were 1837, 1879, 1917 and 1945. From 1985 to 2004, precipitation has experienced longer and more rapid wetting, but the trend of precipitation has decreased in the past few years. The reconstructed series of precipitation is consistent with the historic precipitation/Palmer Drought Severity Index of the western Tianshan Mountains. Here, high precipitation variability occurred during 1770–1800 and 1900‐present, while 1800–1900 was relatively calm. Meanwhile, there was large power in the 2‐ to 7‐year short‐period and over the 34‐ to 35‐ and 40‐ to 43‐year long‐periods. We suggest the precipitation variability may be associated with large‐scale oscillations in the climate system. The reconstruction sheds new light on precipitation variability and the changes in a region where the climate history over the past several centuries is poorly understood.